2017
DOI: 10.2147/lra.s129811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for postdural puncture headache in women undergoing cesarean delivery in Jordan: a retrospective analytical study

Abstract: PurposePostdural puncture headache (PDPH) is one of the most recognized complications after spinal anesthesia in women undergoing cesarean delivery. This study aimed to investigate the incidence of PDPH and its associated risk factors in women undergoing cesarean delivery in Jordan.Patients and methodsThis study included all women who underwent cesarean delivery at King Abdullah University Hospital in Jordan during 2015. Patient characteristics including age, weight, occurrence of PDPH, needle type, repeated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 18 publications
5
24
3
1
Order By: Relevance
“…[ 17 ] No relationship was found between history of past PDPH and occurrence of PDPH. [ 11 18 ] In our study, past PDPH was not associated with occurrence of PDPH. However, we found that previous spinal anaesthesia or previous CD increased the incidence of PDPH.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…[ 17 ] No relationship was found between history of past PDPH and occurrence of PDPH. [ 11 18 ] In our study, past PDPH was not associated with occurrence of PDPH. However, we found that previous spinal anaesthesia or previous CD increased the incidence of PDPH.…”
Section: Discussionmentioning
confidence: 46%
“…The role of past history of PDPH on occurrence of PDPH is conflicting. [ 11 17 18 19 20 ] An increased incidence of PDPH was reported in patients with a history of PDPH (19%) compared with no such history (6.9%). [ 17 ] No relationship was found between history of past PDPH and occurrence of PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 In addition, factors related with the puncture technique (multiple attempts or inadvertent dural puncture during the procedure), with the size of the needle, and with the thickness of the dura seem to change the complication rates in this scenario. 10,11 Finally, the use of anticoagulants in the pre-or postoperative period can lead to higher rates of complications in spinal anesthesia. 7 Often, SDH can present with contralateral paresis and paresthesias, seizures, change of level of consciousness, and severe headache that are not related to orthostatism.…”
Section: Discussionmentioning
confidence: 99%
“…Dies mag daran liegen, dass in beiden Kollektiven die Mehrheit der Punktionen mit einer Nadelgröße kleiner oder gleich 25G durchgeführt wurden. Man kann also konstatieren, dass die Nadelgröße, sofern sie wie in der Literatur empfohlen (25-27G) benutzt wird[7], mittlerweile einen zu vernachlässigenden Risikofaktor darstellt und somit zur Prävention des PKS andere Faktoren in den Vordergrund rücken.Ein gewichtigerer Faktor für das Vorkommen eines PKS könnte die Eigenanamnese der Patienten mit einem häufigen Auftreten von Kopfschmerzen oder Migräne sein[23,24,37,92]. Auch der bereits stattgehabte postspinale Kopfschmerz könnte zu den heute bedeutenderen Risikofaktoren gehören[24,25].…”
unclassified